Comparative study of structural steel and reinforced concrete method : a project management case study - Hu, W.K (University Malaysia Sarawak, UNIMAS., 2004)
Many of our traditional construction methods such as reinforced concrete construction are still greatly favoured by our construction industry. One of the common comment of the usage of structural steel in construction is it is a more expensive option if compared R.C construction. It is the aim of this research study to carry out a comparative study between structural steel construction method with one type of traditional construction method (R.C construction is chosen here)